CT-Scan of Chest among Severe Covid-19 Patients: Experienced from Dedicated Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: High resolution Computed Tomography scan (HR CT-scan) of chest imaging among COVID-19 patients is very useful.Objective: The purpose of the present study was to see the high resolution computed tomography (CT) findings observed among the coronavirus disease 2019 (COVID-19) patients presented with severe pneumonia.Methodology: This retrospective study was performed in the Department of Radiology & Imaging at Kurmitola General Hospital, Dhaka, Bangladesh from April 2020 up to May 2020. As this was a retrospective study, verbal or written consent was not obtained from all potential participants or guardians. The available demographic data as well as the medical history of all data were collected and were thoroughly reviewed from the record book. These patients were RT-PCR confirmed severe cases of COVID-19 patients presented with pneumonia and were admitted in Kurmitola General Hospital, Dhaka, Bangladesh and all these patients underwent HRCT chest.Result: A total number of 155 covid19 patients HRCT scan were evaluated. The mean age with SD of the study population was 58.03±14.08 years. The involvement of both lung was found in 32(20.6%) cases. Fibrosis of lungs and thickening of pleura were found in 38(24.5%) cases and 33(21.3%) cases respectively. Presence of pneumonitis and bronchiectasis were detected in 77(49.7%) cases and 5(3.2%) cases respectively. The most common form was the presence of only ground glass opacities (40.6%).Conclusion: In conclusion the bilateral ground glass opacities and fibrosis of lungs with pneumonitis are most common findings of severe Covid-19 patients.Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):33-37